A.I.’s Black Boxes Just Got a Little Less Mysterious - Roose, Kevin (The New York Times, 2024)
Researchers at the A.I. company Anthropic claim to have found clues about the inner workings of large language models, possibly helping to prevent their misuse and to curb their potential threats.
Keywords: /unread; Anthropic AI LLC; Artificial Intelligence; Computers and the Internet; OpenAI Labs; Research